Collective reputation, social norms, and participation - Saak, Alexander E. (Wiley, 2012)
This paper analyzes a repeated games model of collective reputation with imperfect public monitoring and perfect local peer monitoring of efforts. Even when peer monitoring is local, firms may achieve higher profits under collective reputation by decreasing the cost of maintaining customers' trust. The optimal number of firms that share a common reputation is greater when (1) trades are more frequent and public information is disseminated more rapidly, (2) the deviation gain is smaller compared to the quality premium, (3) customers' information regarding firms' quality is more precise, or (4) intragroup information about firms' quality is more global. From a positive perspective, we suggest how social norms can influence the reputation of regional products. We also offer an efficiency explanation for food scares. From a normative point of view, in our model, protection of geographical indications increases and mandatory traceability decreases welfare and incentives to provide quality without taking into account direct implementation costs.